A clinicoradiographic assessment of 1% metformin gel with platelet-rich fibrin in the treatment of mandibular grade II furcation defects - Parul Sharma; Harpreet Singh Grover; Sujata Surendra Masamatti; Neha Saksena (Wolters Kluwer Medknow Publications, 2017)
Background: Management of furcation defects is challenging, and constantly newer therapeutic strategies are evolving. Platelet-rich fibrin (PRF) is successfully used alone and in combination with various agents in the furcation defects. Lately, metformin (MF), a second generation biguanide has gained popularity owing to its osteogenic potential. Aims and Objectives: The aim of the present study was to evaluate the clinical and radiographic effectiveness of open flap debridement (OFD) and PRF when compared to OFD + PRF + 1% MF gel in the management of mandibular Grade II furcation defects. Materials and Methods: Thirty mandibular grade II furcation defects were stratified into two groups; in one group OFD and PRF is used, and the other group had an additional MF gel with PRF in OFD. Clinical parameters such as plaque index, modified sulcus bleeding index, probing pocket depth (PD), relative vertical attachment level (RVAL), and relative horizontal attachment level (RHAL) were recorded at baseline and at 6 months. Radiovisiography and ImageJ software were used to evaluate the intrabony defect depth. Results: The OFD + PRF + MF group showed significantly higher probing PD reduction, RVAL and RHAL gain than the OFD + PRF group. Conclusions: PRF when combined with a potential osteogenic agent like MF can provide a better therapeutic benefit to a furcation involved tooth.